Expression and Physiology of Voltage-Gated Sodium Channels in Developing Human Inner Ear - Quinn, Rikki K.; Drury, Hannah R.; Cresswell, Ethan T.; Tadros, Melissa A.; Nayagam, Bryony A.; Callister, Robert J.; Brichta, Alan M.; Lim, Rebecca (Frontiers in Neuroscience, 2021)
Sodium channel expression in inner ear afferents is essential for the transmission of vestibular and auditory information to the central nervous system. During development however, there is also a transient expression of Na+ channels in vestibular and auditory hair cells. Here we describe the expression of four Na+ channel genes, SCN5A (Nav1.5), SCN8A (Nav1.6), SCN9A (Nav1.7), and SCN10A (Nav1.8) in the human fetal cristae ampullares, utricle, and base, middle, and apex of the cochlea. Our data show distinct patterns of Na+ channel gene expression with age and between these inner ear organs. In the utricle, there was a general trend toward fold-change increases in expression of SCN8A, SCN9A, SCN10A with age, while the crista exhibited fold-change increases in SCN5A, SCN8A and fold-change decreases in SCN9A and SCN10A. Fold-change differences of each gene in the cochlea were more complex and likely related to distinct patterns of expression based on tonotopy. Generally, the relative expression of SCN genes in the cochlea was greater than that in utricle and cristae ampullares. We also recorded Na+ currents from developing human vestibular hair cells aged 10 – 11 weeks gestation (WG), 12- 13 WG and 14+ WG and found there is a decrease in the number of vestibular hair cells that possess a Na+ current with increasing gestational age. Na+ current properties and responses to the application of tetrodotoxin (TTX) in human fetal vestibular hair cells are consistent with those recorded in other species during embryonic and postnatal development. These results provide a timeline of SCN gene expression and the physiological characterization of Na+ currents in human fetal vestibular and auditory neuroepithelium. Understanding the normal developmental timeline of ion channel gene expression and when cells express functional ion channels is essential information for regenerative technologies.